2023
DOI: 10.1007/s12200-023-00079-y
|View full text |Cite
|
Sign up to set email alerts
|

Generation of dual and quad-optical frequency combs in the injected radiation free mode-locked frequency-shifted feedback laser

Sergey N. Mantsevich,
Ekaterina I. Kostyleva,
Andrey N. Danilin
et al.

Abstract: The results of an optoelectronic system—frequency-shifted feedback (FSF) laser experimental examination are presented. The considered FSF laser is seeded only with optical amplifier spontaneous emission (ASE) and operates in the mode-locked regime, whereby the output radiation is sequence of short pulses with a repetition rate determined by the delay time in its optical feedback circuit. In the frequency domain, the spectrum of such a pulse sequence is an optical frequency comb (OFC). These OFCs we call initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…29,[37][38][39] Here we examine the peculiarities of OFCs generation in FSF laser operating in the mode-locked regime in the absence of an external optical seeding. 40 We apply single AO cell to obtain dual-combs with FSF laser. It was also shown that it is possible to arouse the pair of dual-combs with different spectral spacing between components simultaneously and to generate quad-comb with the interference between these two dual-combs.…”
Section: Introductionmentioning
confidence: 99%
“…29,[37][38][39] Here we examine the peculiarities of OFCs generation in FSF laser operating in the mode-locked regime in the absence of an external optical seeding. 40 We apply single AO cell to obtain dual-combs with FSF laser. It was also shown that it is possible to arouse the pair of dual-combs with different spectral spacing between components simultaneously and to generate quad-comb with the interference between these two dual-combs.…”
Section: Introductionmentioning
confidence: 99%